One pot low-temperature growth of hierarchical δ-MnO2 nanosheets on nickel foam for supercapacitor applications. (10th April 2015) - Pang, Mingjun; Long, Guohui; Jiang, Shang; Ji, Yuan; Han, Wei; Wang, Biao; Liu, Xilong; Xi, Yunlong
Abstract: Hierarchical δ-MnO2 nanosheets as electroactive materials have been directly deposited on nickel foam substrate by one-pot chelation-mediated aqueous method. The morphological evolution process has been investigated by scanning electron microscopy (SEM) at different time intervals in detail. The hierarchical δ-MnO2 electrodes which are synthesized at 30 °C, 40 °C and 50 °C are directly served as binder- and conductive-agent-free electrodes for supercapacitors and have been explored by cyclic voltammetry, galvanostatic charge-discharge test and electrochemical impedance spectroscopy. With the decrease of reaction temperature the specific capacitance of δ-MnO2 electrode increases. The vertically aligned δ-MnO2 nanosheets which have been synthesized at 30 °C exhibit a highest capacitance of 325 F g −1 at the current density of 1 A g −1 . The capacitance loss is less than 15% after 1000 cycles at the scan rate of 30 mV s −1 . Furthermore, it is found that the equivalent series resistance and charge transfer resistance of the electrode are 0.36 Ω and 1.7 Ω, respectively. Such superior electrochemical performance of the electrode made by directly growing porous δ-MnO2 nanosheets on nickel foam makes it has very promising applications in high-performance supercapacitors.